UAVS in Forests and Wildlife Management-An Indian Perspective - Verma, Amit; Verma, Neha (Indian Forester, 2018)
Unmanned Aerial Vehicles (UAVs), initially designed and developed for military use, are making their impact felt in numerous civilian applications now. This is especially true in the field of forestry and wildlife where landscapes are vast, inaccessible and often hostile. UAVs offer a low-cost solution to study such landscapes quickly and often with a perspective which is neither available in ground surveys nor using relatively coarser resolution satellite images. With the miniaturization of electronics, hence the reduction in their sizes and plummeting costs of guidance systems and various sensors, the UAVs offer a viable alternative to the costly aerial surveys and remote sensing images. This paper reviews the application of drones in forest and wildlife management. The recent innovative applications of UAV, in various field like forest fire management, inventory estimates, gap analysis, estimation of fallen timber, wildlife studies, wildlife management and protected area surveillance are pointed. It also discusses the potential application of UAVs for the forest and wildlife management in Indian perspective.